Facilitating of Green Healthy and Safety in Building and Environment for Indonesian Migrant Workers in Penang, Malaysia - Budi Susetyo; Tin Budi Utami; Khozaeni Bin Rahmad (Jurnal Abdimas Indonesia, 2025)
In the recent world, environment become as critical isues, the integration of environmental sustainability into health and safety practices has become more crucial than ever. This paradigm shifted toward Green HSE (Health and Safety Environment) reflects a growing awareness of the interconnectedness between workplace safety, human well-being, and the health. Traditionally, health and safety initiatives have focused primarily on protecting workers from immediate physical hazards. However, a broader perspective acknowledges that the environment in which work occurs is equally critical to long-term well-being. Green HSE recognizes between a healthy environment and the overall health and safety of employees. Green HSE ensures that organizations not only meet these standards but go beyond, demonstrating a commitment to sustainable practices. Sustainable practices often lead to resource efficiency, reduced energy consumption, and operational cost savings, making Green HSE not just environmentally responsible but also economically prudent. This approach ensures a holistic understanding of workplace threats. Implement Green HSE for Indonesian Migran Workers (Pekerja Migran Indonesia/PMI) represents a holistic approach to workplace well-being by recognizing the symbiotic relationship between human health, safety, and environmental sustainability. Facilitating activity can creates a safer, healthier for PMI, and more resilient workplace.